Seismic Evaluation of the Magetan DPRD Building in East Java, Indonesia Using Pushover Analysis - Rohman, Rosyid Kholilur; Wibowo, Rendi Gusta; Afrianto, Arif (Engineering, Technology & Applied Science Research, 2025)
The Magetan Regional People's Representative Council (DPRD) government building was built in 2005 with an irregular Y-shaped pattern. This building is designed based on the SNI 1726:2002 earthquake standard. According to this standard a performance evaluation is necessary. One method to analyze its performance is the pushover analysis, which is a non-linear static analysis method that models the gradual structural response to the lateral loads until the point of collapse. This study aims to evaluate the performance of existing building structures employing pushover analysis to identify the plastic hinges created by different loads and determine the level of structural performance based on the ATC-40 criteria. The structural modeling is performed in the ETABS software, considering the geometric configuration, structural system, and load analysis. The load calculation analysis is carried out according to the SNI 1727:2020 and SNI 1726:2019 standards, including dead loads, live loads, additional dead loads, and earthquake loads. The results of this study suggest an effective modeled base shear force greater than the design shear force. The performance of the building is classified in the Immediate Occupancy (IO) category, indicating resistance and functionality against the earthquake events.